2009
DOI: 10.1017/s1598240800002812
|View full text |Cite
|
Sign up to set email alerts
|

The Transnational Protection Regime and Taiwan's Democratization

Abstract: On September 28, 1986, the Democratic Progressive Party was formed in defiance of restrictions set by a decades-old authoritarian regime, heralding the emergence of a fully competitive multiparty electoral system in Taiwan. Existing literature on Taiwan's democratic breakthrough suggests that international factors have played a significant role in bringing about democracy on the island. But what exactly were these external factors and how have they effected political change in Taiwan? A reexamination of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Indeed, other studies have shown that such linkages are not insignificant political arenas in which bottom-up pressures for democratisation can be generated to compensate for weak external state pressure, or help to generate external state pressure (Ooi 2009 and2013). These are empirically rich case studies that detail social and transnational civil society linkages as interactive arenas in which external democratising pressures are generated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, other studies have shown that such linkages are not insignificant political arenas in which bottom-up pressures for democratisation can be generated to compensate for weak external state pressure, or help to generate external state pressure (Ooi 2009 and2013). These are empirically rich case studies that detail social and transnational civil society linkages as interactive arenas in which external democratising pressures are generated.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis so far implies that the grassroots nature of these forms of linkage may offer a greater potential in heightening the salience of authoritarian government abuse to the West, increase the probability of an international response and strengthening democratic forces in relation to autocrats. Other detailed empirical studies have shown that social and transnational civil society actors that make up such linkages have in other cases generated external pressures that have helped to effect democratisation in Taiwan and South Korea by framing authoritarian abuses as human rights violations (Ooi 2009;2013). Indeed, the Helsinki Process (1973)(1974)(1975) brought about an international normative shift where human rights became a legitimate international concern that could affect interstate relations.…”
mentioning
confidence: 99%